Contrasting intermediation practices in various advisory service networks in the case of the French Ecophyto plan. Issue 3 (27th May 2017) - Cerf, M.; Bail, Le; Lusson, J. M.; Omon, B.
ABSTRACT: Purpose: To highlight the way a public policy aiming to achieve a 50% decrease of pesticides use in France reframed advice provision in public and private networks. Design/methodology/approach: We developed a framework to analyze intermediation in a public funded network, a farmers' association, and a network of co-operatives. The framework captures how advice provision is organized for supporting farmers in redesigning their cropping systems and achieving large-scale farmer participation in such change processes. Findings: (1) All three networks recognize the value of on-farm redesign for pioneers, and the role of farmers' groups but significant differences appear between the networks' intermediary practices and objects; (2) These differences can be related to their way to balance between evidence-based knowledge and farmer's practical experience and ownership of the target; (3) The public DEPHY farm network appears to be an arena in which different advisory models compete; (4) Also specific intermediary practices and objects to involved new farmers in a transition towards less pesticide use were designed, scaling up and out issues are still challenging both public and private advisory organizations. Practical implications: intermediation skills and objects are still to be developed to support on-farm redesign alongside with large-scale farmer participation, and to identify and overcome systemic barriers. Policy makers and advisory boards should clarify their underlying assumptions regarding the triggers for change. Theoretical implications: The framework is a relevant contribution to understand transition in the making and the way AKIS players fail to reassess their underlying assumptions regarding the way to achieve scaling up and out processes. Originality/value: Analyzing relations between public and private networks by exploring the way such networks design and perform intermediation to implement a public policy.